(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the issue of receiving education of talented youth of Turkestan and Bukhara abroad in the 20s of the twentieth century. In particular, the personality and activity, as well as the educational process of TemurbekKazbekov, who was sent from Germany to study in higher and secondary educational institutions from among the youth of the Fergana Valley, was consecrated.